Audition speeches for women - Marlow, Jean (Audition speeches., 2005)
This revised edition contains several new speeches, many of which are taken from plays written and produced during the last five years. There are speeches for a variety of accents and ages to suit all audition requirements. An introductory section contains invaluable comments from directors, casting directors, actors and teachers. Among those contributing are Sir Peter Hall, National Theatre Director and founder of the Royal Shakespeare Company; Robert Palmer, voice teacher at the Royal Academy of Dramatic Art; casting director Doreen Jones; Tim Reynolds, Principal of the Academy Drama Schoo.